Effect of Indole Butyric Acid (IBA) and Thidiazuron (Tdz) Concentrations on Explant Growth Planlet Porang (Amorphophallus muelleri Blume.) In Vitro Culture - Haq, Farhan Chairul; Maftuchah; Zainudin, Agus (Universitas Muhammadiyah Malang, 2022)
Porang (Amorphophallus muelleri Blume.) is a type of tuber plant that is widely available in Indonesia and has tremendous potential and prospects to be developed in Indonesia. Porang is widely exported from Indonesia to several countries. The demand for porang exports continues to increase while the production of porang is still low. In vitro culture is an alternative solution in porang plant propagation to meet the needs of many porang seeds and in a relatively short period of time. Provision of growth regulators in the media can affect the growth of porang. This study aims to obtain information whether there is an interaction between IBA and TDZ in the media, to obtain information on the effect of adding IBA and TDZ with different concentrations on the growth of porang plantlets. This research was conducted using MS medium which was then added with IBA with a concentration of 0.5 ppm, 1 ppm and added PGR TDZ with a concentration of 0.5 ppm, 1 ppm and 1.5 ppm. The results of this study showed that there was no significant difference between the emergence of shoots and the time of emergence of leaves from all treatments. The I1T3 treatment (IBA 0.5 ppm + TDZ 1.5 ppm) was the best combination treatment in this study by showing the fastest root emergence time (6 MSI), the highest average number of shoots (7.25 shoots), the average number of shoots the highest number of roots (3.67 roots), the highest average number of leaves (6 strands) and the highest average shoot height (1.33 cm).